Role of ontology in software testing. Issue 2 (17th February 2020) - Sharma, Shilpa; Raja, Linesh; Bhatt, Devershi Pallavi
Abstract: Software testing is a multifaceted and essential method to achieve the quality of product. Its significance has been increasing and well accepted, so there is an emergent concern in improving the attainment of this practice. In this perspective, Knowledge Management (KM) emerged as an key sustaining method for improving the software testing process. However, managing relevant testing knowledge according to the influencing factors requires an effective way to represent and to correlate to a huge number of testing aspects. To address this concern, we have analyzed an impact of ontology on software testing across influenced asects of software testing. Ontology provides a standard conceptualization of the software testing domain that can construct a knowledge base, establishing a common vocabulary for knowledge owners about the testing domain, structured testing knowledge databases, identification of testing knowledge objects, and making it easier to search for relevant information. In this paper, we present factors affecting software testing direct or indirect influenced aspects. Moreover, we discuss how ontology helps in alleviating the software testing.